Investigation of Design, Manufacturing and Performance of Light Metal Matrix Composite Material Production System - Sur, Gökhan; Kayabaşi, İsmail (Gazi University, 2019)
In this study, a production unit for light metal based particle reinforced composite material with stir casting technique was designed, manufactured and experiments related to performance have been carried out. In production system design, it is aimed to provide ease of use and ergonomics of usage compared to similar ones. In line with this objective, the size and location of the melting furnace and the mixing system were determined, a compact design of the reinforcing element with mechanical and electrical components related to the movement of the melting pot in / out of the furnace. In the performance tests of the unit, the characteristics of melting the matrix material and obtaining homogeneous particle distribution in the production of composite material were investigated. For this purpose; one unreinforced AA 6060 aluminum alloy material and SiC particle reinforced AA 6060 matrix two composites were manufactured. Average particle size 200 mesh SiC particles were used in the production of composites. The volume of SiC reinforcing ratio of the manufactured composites is 7% and 10%. Microstructure, density and hardness properties of the produced samples were investigated in the direction of the unit's performance tests. According to the microstructure analysis, it has been observed that composite with metal matrix is homogeneous in part. According to the hardness analysis, it has been identified that metal matrix composite containing 10% SiC has the highest hardness. As a result of the density measurement, as the volume of the reinforcement ratio in the metal matrix composite with SiC reinforcement increases, the density and porosity of the material increases.
Keywords: Science (General); Science; Q; Stir casting technique; Mechanical properties; Composite materials; Micro structure; Engineering (General). Civil engineering (General); Metal matrix composite; Q1-390; Stir casting technique Micro structure Mechanical properties; Micro structure Mechanical properties; Metal matrix composite Stir casting technique Micro structure Mechanical properties; TA1-2040